A historical surface climate dataset from station observations in Mediterranean North Africa and Middle East areas. (22nd April 2014) - Brunet, Manola; Gilabert, Alba; Jones, Phil
<x xml:space="preserve">Abstract</x> Historical climatic data from station observations taken in North African and Middle East Mediterranean countries since the second half of the 19th century have been digitized and quality‐controlled in the framework of the EU‐funded European Reanalysis and Observations for Monitoring (EURO4M) project. Daily maximum and minimum temperatures and precipitation totals, along with sub‐daily data for surface air pressure have been recovered by using historical data sources involving book/logbook collections archived in national and international data centres. The new dataset produced comprises climatic time series for 79 stations that have operated in southern and eastern Mediterranean countries. While the developed time series have data gaps, every effort has been made to infill these gaps, to improve assessments of the long‐term changes in climate variability in the region.